Acculturation Processes of Hmong in Eastern Wisconsin - John Kha Lee (Hmong Studies Journal, 2010)
This study examines acculturation processes among Hmong who live in Eastern Wisconsin by using the East Asian Acculturation Measure (EAAM), which was developed by Barry (2001). The results indicated that in terms of Acculturation, Hmong ranked highest in integration, then separation, assimilation, and lastly marginalization. Questions on each dimension of integration, separation, assimilation, and marginalization were analyzed and positive correlations were found between the youngest of the generations, the length of residency in the United States, and the ability to speak, read, and write in English. In contrast, the older the age of the participant when they came to the United States had a positive correlation with separation. The ability to speak, read, and write in English had a positive correlation with assimilation, and the older the age of coming to the United States had a positive correlation with marginalization. Assimilation and separation had a positive correlation with marginalization, while integration had a negative correlation with marginalization and a positive correlation with assimilation, and separation had no correlation with marginalization. Results are discussed in regards to previous Hmong acculturation studies.